Testing the Effectiveness of Correction Placement and Type on Instagram. (October 2020) - Vraga, Emily K.; Kim, Sojung Claire; Cook, John; Bode, Leticia
Despite concerns about misinformation across social media platforms, little attention has been paid to how to correct misinformation on visual platforms like Instagram. This study uses an experimental design on a national sample to test two features of user-based correction strategies on Instagram for a divisive issue on which misinformation abounds: the issue of climate change. First, we unite the inoculation and correction literature to test the efficacy of prebunking corrections that come before exposure to the misinformation versus debunking strategies that occur after exposure. Second, we compare fact-focused corrections that provide accurate information to rebut the misinformation against logic-focused corrections that highlight the rhetorical flaw underpinning the misinformation. Our findings suggest that these strategies intersect to reduce misperceptions. Logic-focused corrections effectively reduce misperceptions regardless of their placement before or after the misinformation, and appear to function in part by reducing perceptions of the credibility of the misinformation post. Fact-focused corrections only reduce misperceptions when they occur after the misinformation, but are seen as more credible than logic-focused corrections. We discuss the implications of our findings for understanding the theoretical mechanism by which correction can occur and the practical guidelines to best correct misinformation in visual social media spaces.